The Emerging Trend of Bio-Engineering Approaches for Microbial Nanomaterial Synthesis and Its Applications - Dhanker, Raunak; Hussain, Touseef; Tyagi, Priyanka; Singh, Kawal Jeet; Kamble, Shashank S. (Frontiers in Microbiology, 2021)
Micro-organisms colonized the world before the multi-cellular organisms evolved. With the advent of microscopy, their existence became evident to mankind and also the vast processes they regulate, that are in the direct interest of human beings. One such process that intrigued the researchers is the ability to grow in presence of toxic metals. The process seemed to be simple with the metal ions being sequestrated into the inclusion bodies or cell surfaces enabling the conversion into nontoxic nanostructures. However, the discovery of genome sequencing techniques highlighted the genetic makeup of these microbes as a quintessential aspect of this phenomenon. The findings of Metal Resistance Genes (MRG) in these microbes showed a rather complex regulation of these processes. Since most of these MRGs are plasmid-encoded they can be transferred horizontally. With the discovery of nanoparticles and their many applications from polymer chemistry to drug delivery, the demand for innovative techniques of nanoparticle synthesis increased dramatically. It is now established that microbial synthesis of nanoparticles provides numerous advantages over the existing chemical methods. However, it is the explicit use of biotechnology, molecular biology, metabolic engineering, synthetic biology, and genetic engineering tools that revolutionized the world of microbial nanotechnology. A detailed study of the micro and even nano level assembly of microbial life also intrigued biologists and engineers to generate molecular motors that mimic bacterial flagellar motor. In this review, we highlight the importance and tremendous hidden potential of genetic engineering tools in exploiting the area of microbial nanoparticle synthesis. We also highlight the application-oriented specific modulations that can be done in the stages involved in the synthesis of these nanoparticles. Finally, the role of these nanoparticles in the natural ecosystem is also addressed.